TEACHER EDUCATION WITHIN THE CONTEXT OF EDUCATION PERMANENTE - Paré, Leo (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1978)
The following excerpts from a speech delivered to the Faculty of Education at McGill University, 18th October 1977, will be of interest to readers teaching in the Province of Québec, as it was delivered by the gentleman in the Government of Québec who is in the best position to influence teacher education in the Province.